KAJIAN ISLAM DI BARAT - Ali Romdhoni (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2012)
The rise of Islamic studies in the West countries contributes in the richness of Islamic heritage that can be approached scientifically and critically. In addition, it is quite possible that it will gradually shift and belong to another society. By applying the theory of literature-ethnography the writer tries to understand how the orientalists consider Islam as the object of the study through observation of daily life phenomena and its documentation. Based on the analysis, it is found that Islam becomes the object of study not only among Muslims society but also among others especially the orientalists whose different goals and interests. Similarly, the approach used in the Islamic studies is also different.